A new designed hydrazine group-containing ruthenium complex used for catalytic hydrogenation of esters1. Issue 61 (7th August 2015) - Tan, Xuefeng; Wang, Qingli; Liu, Yuanhua; Wang, Fangyuan; Lv, Hui; Zhang, Xumu
<x xml:space="preserve">Abstract</x> Hydrazine group-containing nitrogen–phosphine ruthenium complexes were synthesized and used for hydrogenation of esters, and excellent performance was observed (TON up to 17 200).